1985
DOI: 10.1159/000226041
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of Serum Ferritin Measurements in Patients with Testicular Germ Cell Tumors

Abstract: In 50 patients with seminoma and in 50 with nonseminomatous germ cell tumors of the testis, serum levels of conventional markers (CEA, AFP, hCG) and ferritin were measured at the time of admission and during management. The conventional markers behaved as reported previously. After orchiectomy, elevated levels of ferritin were found in the presence as well as in the absence of tumor; the extent of these elevations was highly variable. Serial determinations of serum ferritin showed two patterns of variation. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…These correlations suggest that serum ferritin may be useful in the initial clinical evaluation and in the assessment of response to therapy in patients with acute leukemia and malignant lymphoma . Szymendera et al and Volpino et al found that measuring serum ferritin levels is a useful clinical indicator in patients with testicular germ‐cell tumors and lung cancer, respectively. Moreover, it is found that melanoma cells can secrete ferritin, which contributes to the progression of melanoma…”
Section: Ferritin As a Tumor Markermentioning
confidence: 98%
“…These correlations suggest that serum ferritin may be useful in the initial clinical evaluation and in the assessment of response to therapy in patients with acute leukemia and malignant lymphoma . Szymendera et al and Volpino et al found that measuring serum ferritin levels is a useful clinical indicator in patients with testicular germ‐cell tumors and lung cancer, respectively. Moreover, it is found that melanoma cells can secrete ferritin, which contributes to the progression of melanoma…”
Section: Ferritin As a Tumor Markermentioning
confidence: 98%